Hubungan Antara Tingkat Pemahaman dan Sikap Masyarakat Kota Jambi Terhadap Kewajiban Zakat dengain Kesadaran untuk Berzakat ke BAZDA - Abuzar, Abuzar (Kontekstualita: Jurnal Penelitian Sosial Keagamaan, 2006)
This article describes the peoples understanding and their attitude on the obligation to pay the zakat (alms) toward their willingness to pay the zakat (alms) into Bazda (Agency for collecting and distributing zakat and shadaqah). This research is qualitative-statistic in nature and employs correlation analytical and linear regression approaches. It is found that the awareness and the willingness of Moslem to pay the zakat (alms) is significantly high but their willingness to channel their zakat (alms) through bazda is still low. It is because of their distrust into the management of this Bazda as it is poor-managed leading to its failure to increase the prosperity of the needy in the society.